Pertanggungjawaban Hukum Badan Pertanahan Nasional Terhadap Keberadaan Sertifikat Ganda - Tanner, Juliani; Salmon, Hendrik; Pattinasarany, Yohanes (CAPITAN: Constitutional Law & Administrative Law Review, 2023)
Certificate of land rights as a product of land registration which provides legal certainty and legal protection to persons or legal entities. However, sometimes more than one certificate is issued by the National Land Agency which results in multiple certificates. This writing aims to find out how the legal responsibility of the National Land Agency is for the existence of multiple certificates. This research is a normative juridical research by means of research conducted by collecting primary, secondary, tertiary data obtained by using library research. The results of the study show that the legal responsibility of the land agency if there are multiple certificates is carried out in the form of legal responsibility in the aspects of civil law and administrative law. Legal responsibility in the aspect of civil law, When the land agency issues a certificate resulting in the appearance of multiple certificates which results in a loss to the parties to the said certificate, it is obligatory to compensate for the intended loss. Meanwhile, the legal responsibility of the land agency from the legal aspect of state administration is based on the granting of authority to the land agency to issue certificates of land rights. Every agency or official in exercising authority must be responsible for its implementation. Implementation of legal responsibility from the legal aspect of state administration through the act of canceling the intended certificate. As well as the legal consequences for officials of the national land agency if there is a double certificate, there are sanctions for the land agency official who issues the certificate which results in a double certificate.